Antimalarial and antioxidant activity of phenolic compounds isolated from Erythrina crista-galli L. - Tjahjandarie, Tjitjik Srie (Journal of Chemical And Pharmaceutical Reseach 3/668 Ma;viya Nagar, Jalpur Rajasthan, India-3020I7, 2014)
Threephenolic compounds, phaseollidin (1), sandwicensin (2), and lonchocarpol A (3) had been isolated from the stem bark of Erythrina crista-galli. Their structures were established on the basis of spectroscopic evidence. Compounds 1–3 were evaluated for their antimalarial properties against Plasmodium palcifarum, showing their IC were 1.66, 1.83, and 1.69 µg/mL.The antioxidant activity of 1–3 against 2,2-diphenyl-1-picrylhydrazyl (DPPH), showing their IC50 were 209.4,305.6,and 1115.7 µM, respectively.